Music and Altered States : Consciousness, Transcendence, Therapy and Addictions. - Aldridge, David, 1947- (Jessica Kingsley Publishers, 2005)
This international collection examines the opportunities for using music-induced states of altered consciousness to promote physical and mental healing, treat substance dependence, and in spiritual and palliative care. The contributors describe the successful use of altered states and their therapeutic potential, providing examples from different cultures and clinical, therapeutic and spiritual settings. Their observations cover a wide range of music types capable of inducing altered states, including polyrhythmic music, monotonous drumming, Western pop, and Arab musical schemata, complemented.